Effect of three pre-drying treatments and two drying methods on the quality of scotch bonnet (capsicum chinense) grown in the Tolon/Kumbungu District of Northern Ghana - Sualihu, Alhassan (2014)
A dissertation submitted to the, Kwame Nkrumah University of Science And Technology, in partial fulfilment of the requirements for the award of Master of Science (Phil. Postharvest Technology) degree.